PEMANFAATAN LIMBAH SERUTAN KAYU NANGKA (Artocarpus heterophyllus) UNTUK PEWARNAAN KAIN SUTERA - Rosyida, Ainur; Subiyati, Subiyati (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2018)
This research aimed to exploit the jackfruit wood  waste as textile coloration on silk. Moreover to know influence of dip solution pH variation application and mordan process to dyeing result quality. The dying process obtained by differences pH variation and fixator substance, namely alum and ferrous sulfate. According to the research was known that jackfruit wood  could be used to color silk into yellow and brown. The final color depending on the fixator whereas the color density and trend color depending on pH solution used in dyeing process. The dyeing process proved the good result, since it got smooth and permanent color. The color density showed the dyeing process using alum mordant got yellow included the highest color density on acid (pH : 5) whereas the ferrous sulfate got brown included the highest color density on acid (pH : 5). The color endurance on washing process got good color change value on 4 -5 of Grey Scale standart and of Staining Scale standard. Whereas color endurance on dry rubbing got very good: 5 on wet rubbing of Grey Scale standard. The results of this study can be applied to the process of dyeing natural dyes with optimal results and a short time.